Faktor Internal yang Mempengaruhi Likuiditas Bank Syariah: Analisis Rasio Capital Adequacy Ratio (CAR), Dana Pihak Ketiga (DPK), Non Performing Financing (NPF) - Iin Emy Prastiwi; Muhammad Tho'in; Oktaviani Alvita Kusumawati (ITB AAS INDONESIA Surakarta, 2021)
This research was conducted with the aim to do an empirical analysis of the Study Liquidity at PT Bank BNI Syariah 2011-2019 Period. This study discusses the ratio of CAR, DPK, and NPF to Liquidity both simultaneously and simultaneously at PT Bank BNI Syariah. This type of research in this thesis uses quantitative research with the data used are secondary data and quarterly report data for all the variables and financial ratios required in the BNI Syariah financial statements for 2011-2019. Data analysis methods used are descriptive statistical tests, classic assumptions test, and hypothesis testing conducted by multiple regression analysis. The results of the t-test (partial test) showed that CAR and DPK variables were not significant to Liquidity, while the NPF variable was influential and negative significant to Liquidity. The results of the F-test (simultaneous test) showed that CAR, DPK and NPF variables had a significant effect on liquidity. In terms of R-Square values the CAR, DPK and NPF variables have a proportion of Liquidity of 22,6%.